The Twenty-Year Trajectory of Suicidal Activity Among Post-Hospital Psychiatric Men and Women with Mood Disorders and Schizophrenia. Issue 3 (2nd July 2016) - Kaplan, Kalman J.; Harrow, Martin; Clews, Kelsey
Abstract : The Chicago Follow-up Study has followed the course of severe mental illness among psychiatric patients for more than 20 years after their index hospitalization. Among these patients are 97 schizophrenia patients, 45 patients with schizoaffective disorders, 102 patients with unipolar nonpsychotic depression, and 53 patients with a bipolar disorder. Maximum suicidal activity (suicidal ideation, suicidal attempts and suicide completions) generally declines over the 3 time periods (early, middle, and late follow-ups) following discharge from the acute psychiatric hospitalization for both males and females across diagnostic categories with two exceptions: female schizophrenia patients and female bipolar patients. A weighted mean suicidal activity score tended to decrease across follow-ups for male patients in the schizophrenia, schizoaffective, and depressive diagnostic groups with an uneven trend in this direction for the male bipolars. No such pattern emerges for our female patients except for female depressives. Males' suicidal activity seems more triggered by psychotic symptoms and potential chronic disability while females' suicidal activity seems more triggered by affective symptoms.